Analysis of Winnowing Algorithms in The Title Selection System of Job Training Report, Faculty of Engineering, Universitas Malikussaleh - Rizal; Defry Hamdhana (Faculty of Engineering, Malikussaleh University, 2018)
The number of practical work reports that have been published by department makes a coordinator of on the job training have difficulty in determining the feasibility of the title of the on the job training report quickly. This happened because each report that was made must be unique in terms of the methods and objects that are examined in a particular institution/company. So that reports that have been published previously did not experience plagiarism. Winnowing algorithm is an algorithm used to detect the similarity of words/sentences in two or more texts that are compared. If there are two texts that are the same, a fingerprint will be formed. So that the practical work coordinator can determine the feasibility of the title of on the job training report quickly and the creation of an online-based on the job training report information system that can be accessed at any time.